Current advances in membranes for competent hydrogen purification: A short review - Mohd Syafiq, Sharip; Norazlianie, Sazali; Mohd Nizar, Mhd Razali; Farhana, Aziz; Mohd Hafiz Dzarfan, Othman (SpringerLink, 2019)
Hydrogen (H2) has been recognized as the clean potent energy carrier to pacify the worldwide energy and environmental problem. The tremendously escalate of high-quality hydrogen urge the development of membrane technology for hydrogen separation that believe have high potential and advantages compare to the conventional hydrogen separation technique. In correlation, the growing of research field like chemical and material sciences, membrane sciences and technology, and advance membrane technology over the decade provides important information on the membrane technology for hydrogen separation. Moreover, the present review was set up as the preliminary study and guidance for the future research and development of membrane materials and membranes for hydrogen purification, and hence promote the development of sustainable and clean hydrogen energy.